WE4.5 Meta-analysis of the outcomes of Trans Rectus Sheath Extra-Peritoneal Procedure (TREPP) for inguinal hernia. (9th August 2022) - Anwer, Amal Azhar; Hajibandeh, Shahab; Hajibandeh, Shahin; Evans, Louis; Naguib, Nader Naeem; Havard, Tim; Helmy, Ahmed Hazem
Abstract: Aims: To evaluate the outcomes of Trans Rectus Sheath Extra-Peritoneal Procedure (TREPP) in patients undergoing elective inguinal hernia repair Methods: In compliance with PRISMA statement standards, electronic databases were searched to identify all studies reporting the outcomes of TREPP in patients undergoing elective inguinal hernia repair. The outcomes of interest included recurrence, chronic pain, haematoma, and wound infection. Proportion meta-analysis model was constructed to quantify the risk of postoperative complications and direct comparison meta-analysis model was constructed to compare the outcomes of TREPP and other open techniques. Random-effects modelling was applied to calculate pooled outcome data. Results: Seven studies enrolling 1891 patients undergoing TREPP were included. Pooled analyses showed that TREPP was associated with 3.00% (95% CI 1.00–6.00%) risk of recurrence, 3.00% (95% CI 2.00–6.00%) risk of chronic pain, 8.00% (95% CI 0.00–20.00%) risk of haematoma, and 3.00% (95% CI 0.00–6.00%) risk of wound infection. The results remained consistent through subgroup analysis of patients with primary hernias and those with recurrent hernias. Analysis of a limited number of comparative studies showed no difference between TREPP and Lichtenstein technique in terms of recurrence (OR: 1.57, P=0.26) and chronic pain (OR: 1.16, P=0.59). Conclusions: The best available evidence suggests that TREPP may be a promising technique for elective repair of inguinal hernias as indicated by low risks of recurrence, chronic pain, haematoma, and wound infection. Moreover, there is a lack of comparative evidence on outcomes of TREPP versus other techniques highlighting a need for high quality randomised controlled trials for definite conclusions.